Art Discourse in Modern Fine Arts in Surabaya: An Analytical Historical Research - Djatiprambudi, Djuli; Sampurno, Muchammad Bayu Tejo (Harmonia: Journal of Arts Research and Education, 2023)
This research aims to understand the art discourse that is the foundation for developing modern fine arts in Surabaya. Art discourse represents the fundamental ideas behind the creation of artworks, which are developed and dialectically discussed within the context of the art ecosystem in Surabaya. The research design is based on an analytical, historical research method with a sociohistorical approach. The findings reveal the existence of continuity and change in art discourse from the Aksera generation (Academy of Fine Arts Surabaya) in the 1970s to the post-Aksera generations, namely the 1980s and 1990s generations. Three bases of art discourse emerged as the core expressions of aesthetics in modern fine arts in Surabaya during the 1970s to 1990s: 1. The discourse of nationalism (identity) underlies the art discourse of the Aksera generation; 2. The discourse of the market (commodification of art) becomes the main concern of the 1980s generation; 3. The social-political discourse serves as the platform for the art discourse of the 1990s generation. These three discourses demonstrate similarities and differences within the context of art discourse that evolved in modern fine arts in Indonesia.